Rancang Bangun Website Klasikfikasi Untuk Pencarian Produk Pasar Online Berdasarkan - Danny Sebastian (Maranatha University Press, 2017)
In the past few years, online marketplace has improved so fast. There are many product listed at online marketplace. This growth make a new problem for buyers, it’s too much information. Which is too many online marketplaces and products listed online. From the above problems, came the idea for making a website that could help user to search multiple online marketplace at once, and help the user find the desired products. In this research will be generated website design that can help buyers to find products that their desired. The website will be able to do a certain classification by using classification algorithm, K-Nearest Neighbor.